DC Discharge Plasma Polymerization of 1-Naphthylamine - Yablokov, M.; Gilman, A.; Surin, N.; Augustyniak-Jablokow, M.; Tadyszak, K.; Kuznetsov, A. (International Conference on Plasma Surface Engineering, 2013)
Not available